2010
DOI: 10.3171/2009.12.jns09689
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular glutamate measured by cerebral microdialysis in severe traumatic brain injury

Abstract: Object Authors of several studies have implied a key role of glutamate, an excitatory amino acid, in the pathophysiology of traumatic brain injury (TBI). However, the place of glutamate measurement in clinical practice and its impact on the management of TBI has yet to be elucidated. The authors’ objective in the present study was to evaluate glutamate levels in TBI, analyzing the factors affecting them and determining their prognostic value. Methods A prospective study of patients with severe TBI was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(148 citation statements)
references
References 18 publications
4
141
1
2
Order By: Relevance
“…In contrast to our findings, Brown et al, 199825 showed that despite the persistent increase in the CSF glutamate levels up to 5 days after severe TBI, these changes did not predict brain death or correlate with GCS and electrophysiological deterioration. However, the majority of clinical studies indicate that increased brain extracellular glutamate levels in association with comorbidities may predict poor functional outcomes and brain death 11, 12, 13, 14. For instance, secondary mechanisms associated with the brain tissue deformation including global ischemia, sustained increased intracranial pressure and focal contusions11, 13, and spontaneous brain hypothermia (<36°C)26 have been implicated in the increase in glutamate levels and acute neuronal death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, Brown et al, 199825 showed that despite the persistent increase in the CSF glutamate levels up to 5 days after severe TBI, these changes did not predict brain death or correlate with GCS and electrophysiological deterioration. However, the majority of clinical studies indicate that increased brain extracellular glutamate levels in association with comorbidities may predict poor functional outcomes and brain death 11, 12, 13, 14. For instance, secondary mechanisms associated with the brain tissue deformation including global ischemia, sustained increased intracranial pressure and focal contusions11, 13, and spontaneous brain hypothermia (<36°C)26 have been implicated in the increase in glutamate levels and acute neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, high concentrations of extracellular glutamate are commonly observed after severe TBI, the magnitude of which correlates with increased intracranial pressure (ICP) and poor clinical outcomes 11, 12, 13, 14. Immediately after TBI, there is an exacerbated glutamate‐induced neuronal calcium influx and ionic imbalance, which evokes membrane depolarization and further glutamate release.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, a multitude of studies have detected significant increases in extracellular glutamate levels in the days following injury, with some reports correlating increases in extracellular glutamate with unfavorable outcomes (Bullock et al, 1995Chamoun et al, 2010;Hlatky et al, 2004;Hutchinson et al, 2002;Koura et al, 1998;Persson and Hillered 1992;Reinert et al, 2000;Timofeev et al, 2011;Vespa et al, 1998;Yamamoto et al, 1999). These studies emphasize the significance of glutamate dysregulation in the acute pathophysiology and consequences of TBI.…”
Section: Introductionmentioning
confidence: 93%
“…Increased glutamate concentration in the extracellular compartment can be toxic to neurons [47]. Increase in the extracellular concentration of glutamate in the case of CNS injury or disease has been linked to a number of potential mechanisms including excessive release and impaired cellular uptake.…”
Section: Signalling Roles Of Ca2+ and Rosmentioning
confidence: 99%